The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0103-97332006000600059
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the current density and resistivity on the optical properties of p-type porous silicon thin films fabricated by the electrochemical anodizing method

Abstract: Porous Silicon thin films were produced in this work by the electrochemical anodizing method. The samples were fabricated anodizing p type Si substrates with different resistivities in hydrofluoric acid. Samples were prepared at different current densities. The films were characterized through reflectance and room photoluminescence (PL) measurements in the visible region. A simple theoretical model is proposed to calculate the Optical constants of the material using a theoretical simulation of the reflectance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
1
0
0
Order By: Relevance
“…Thus, the observed optical anisotropy of the porous silicon surfaces is not unexpected. As to the values of the obtained refractive indices, similar results were reported in refs .…”
Section: Resultssupporting
confidence: 88%
“…Thus, the observed optical anisotropy of the porous silicon surfaces is not unexpected. As to the values of the obtained refractive indices, similar results were reported in refs .…”
Section: Resultssupporting
confidence: 88%
“…Etch rate increases with current density, since a higher current density provides an increase in the number of charge carriers, and thereby the rate of charge exchange across the interface. The mechanisms on the PL of PS films are still in debate [3][4][5][6][7][8][9][10]. It is safe to conclude at this stage that the PL spectrum of the anodized PS films is independent on the anodization current density for our p-type silicon.…”
Section: Resultsmentioning
confidence: 87%
“…For example, Ohmukai et al observed that both the peak wavelength of the photoluminescence (PL) and the size of the silicon nanocrystals evolve with the anodization current density in the range of 2-100 mA/cm 2 [2]. Torres et al studied the influence of the current density on the PL properties of p-type PS films fabricated by the electrochemical anodizing method [3]. They reported the peak wavelength of the PL spectra of samples prepared on 0.01 Ω⋅cm substrates, at different anodizing currents, are shifted toward shorter wavelengths as the anodizing current increases.…”
Section: Introductionmentioning
confidence: 99%